Arthroscopic Linear Chain Fixation for the Treatment of Medial Meniscus Posterior Root Tear: A Case Study - Jing‐qing Chen; Hai‐yun Niu; Ming Li; Zhen‐yue Dong; Ju‐yuan Gu; Wei‐xia Bai; Bai‐cheng Chen (Orthopaedic Surgery, 2024)
Background The repair and reconstruction of medial meniscus posterior root tears (MMPRTs) is an important issue in the field of orthopedic sports medicine. This study reports the first application of arthroscopic linear chain fixation for the treatment of MMPRTs. Case presentation A 78‐year‐old female patient presented with a 1.5‐month history of right knee pain accompanied by a locked facet joint. The patient underwent surgery with the new linear chain fixation method. In this method, the suture and the loop part of the buckle‐strap titanium plate were combined into a linear chain mechanical complex, and the tension of the posterior root stump was gradually increased by pulling on the two attachment lines at the external mouth of the tibial tunnel. The postoperative Lysholm score was 89, and the visual analogue scale score was 0.9, indicating a significant improvement in knee joint function. At the 7‐month and 1‐year post‐surgery follow‐up, physical and MRI examinations confirmed satisfactory healing of the MMPRTs. Conclusion This surgical approach offers several benefits, including a simplified instrumentation setup, preservation of natural anatomical structures, and reliable residual stump fixation. It has the potential for clinical implementation.